Do we need memory to set goals? (London Journal of Research In Humanities and Social Sciences, 2023)
Based on the narrative complexity of Memento, this essay delves into Leonard’s condition of being unable to form long-term memories. Despite this limitation, Leonard’s capacity to set and pursue goals remains intact, fueled by his unwavering quest for vengeance following his wife’s murder. Drawing parallels between Leonard’s situation and Albert Camus’ description of Sisyphus, the essay argues that both characters acknowledge, embrace, and rebel against absurdity by maintaining a persistent goal.
Keywords: memento; leonard; film analysis; memory; goals; sisyphus; camus; locke